LOW VULNERABILITY OF THE POSTERIOR EYE SEGMENT TO SARS-COV-2 INFECTION: Chorioretinal SARS-CoV-2 Vulnerability. Issue 2 (February 2022) - Künzel, Steffen Emil; Bürgel, Thore; Künzel, Sandrine Helene; Pohlmann, Dominika; Zeitz, Oliver; Joussen, Antonia; Dubrac, Alexandre
Abstract : Purpose: Retinal manifestations have been described in COVID-19 patients, but it is unknown whether SARS-CoV-2, the causal agent in COVID-19, can directly infect posterior ocular tissues. Here, we investigate SARS-CoV-2 host factor gene expression levels and their distribution across retinal and choroidal cell types. Methods: Query of single-cell RNA sequencing data from human retina and choroid. Results: We find no relevant expression of two key genes involved in SARS-CoV-2 entry, ACE2 and TMPRSS2, in retinal cell types. By contrast, scarce expression levels could be detected in choroidal vascular cells. Conclusion: Given the current understanding of viral host cell entry, these findings suggest a low vulnerability of the posterior eye segment to SARS-CoV-2 with a potential weak spot in the vasculature, which could play a putative causative role in ocular lesions in COVID-19 patients. This may qualify the vasculature of the human posterior eye segment as an in vivo biomarker for life-threatening vascular occlusions in COVID-19 patients. Abstract : Supplemental Digital Content is Available in the Text.Given the current understanding of viral host cell entry, this single-cell RNA analysis of the human retina and choroid suggests a low vulnerability of the posterior eye segment to SARS-CoV-2 infection with a potential weak spot in the choroidal vasculature.